2018
DOI: 10.3762/bjnano.9.86
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin inhibits zinc corrosion by destabilizing point defect formation in the oxide layer

Abstract: Corrosion inhibitors are added in low concentrations to corrosive solutions for reducing the corrosion rate of a metallic material. Their mechanism of action is typically the blocking of free metal surface by adsorption, thus slowing down dissolution. This work uses electrochemical impedance spectroscopy to show the cyclic oligosaccharide β-cyclodextrin (β-CD) to inhibit corrosion of zinc in 0.1M chloride with an inhibition efficiency of up to 85%. Only a monomolecular adsorption layer of β-CD is present on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…The hydrophobic MBT cannot incorporate into the aqueous corrosion products of zinc, which are formed in chloride during the preparation step of the pretreatment film. Although our group has recently reported that β-CD acts as a corrosion inhibitor by itself, its inhibition efficiency is rather low at chloride concentrations of 0.5 M and above . Consequently, β-CD itself is likely not directly contributing to the inhibition.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The hydrophobic MBT cannot incorporate into the aqueous corrosion products of zinc, which are formed in chloride during the preparation step of the pretreatment film. Although our group has recently reported that β-CD acts as a corrosion inhibitor by itself, its inhibition efficiency is rather low at chloride concentrations of 0.5 M and above . Consequently, β-CD itself is likely not directly contributing to the inhibition.…”
Section: Resultsmentioning
confidence: 88%
“…26 β-CD itself acts as corrosion inhibitor for zinc in the presence of up to 0.1M chloride. 27 Zinc is widely used as metallic coating for steels, and to a lesser extend also on aluminum alloys. As opposed to the situation investigated for one class of aluminum alloys in above mentioned works employing inhibitor release systems where localized corrosion is dominant, [23][24][25] uniform corrosion dominates corrosion of zinc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, reactive fresh zinc surface under exposure to the atmosphere subsequently formed dense, adherent corrosion byproducts, leading to 10- to 100-fold decrease in the rate of corrosion than ferrous materials depending on the environment. These corrosion products develop rapidly on metal surface as the coating and act as an additional barrier between the metal and the environment, which might make it a well-suited corrosion protective coating for metal products [33]. Thus, in highly oxidizing condition, zinc might limit reactions occurring on the titanium oxide layer of Ti-NW-Zn, which protects the titanium substrates.…”
Section: Resultsmentioning
confidence: 99%
“…[17] Inhibition effects can also be caused by a rather intricate influence on the defect structure of the forming oxide. [38] The cathodic processes are not affected by the BDs, as evidenced by the good agreement of the cathodic polarisation curves in the presence and absence of BDs. Therefore, the decreased corrosion rate must be caused by an effect on the anodic processes, which implies that a component from the BDs acts like an anodic corrosion inhibitor.…”
Section: Carbon Steelmentioning
confidence: 81%